(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
The paper aims to analyze the workshop “The coat of Marx,” designed and coordinated by Maira Gouveia. The workshop is an action inspired by the coat’s poetics overlays with its users reported in Peter Stallybrass’s same title’s book (2012). As a methodology, the workshop has a practical-reflective character. It proposes exercises that dialogue with the fields of semiotics and anthropology, using questions and reflections from fashion theory and the field of design to weave a critical-reflective reading on the possibilities of relationships to be built with everyday objects. Throughout the investigation, it was possible to observe ways of occurring dialogues between design, fashion, anthropology, and semiotics to rethink our look at material culture. Moreover, the workshop proposes a more significant relationship with the artifacts surrounding us, from Karen Barad’s agential realism to think in the workshop, the possibility of understanding objects as social agents as co-creators of our ways of living.